Tlhotlhomisi ya dintshontsho tsa lorato : L.D. Raditladi (Setswana) - Mojalefa, M.J. (Mawatle Jeremiah), 1948- (University of Pretoria, 2013)
Dissertation (MA (Setswana))--University of Pretoria, 2007.